DETECTION OF CAMPYLOBACTER SPP. IN FRESH CHICKEN MEAT USING DIFFERENT CULTURING PROTOCOLS - Kritsiriwuthinan, Kanyanan; Jantrapanukorn, Bajaree; Choosang, Kanthima; Thawonwan, Unchana (Interprofessional Journal of Health Sciences, 2023)
This study aimed to compare different culturing protocols for detecting Campylobacter spp. in fresh chicken meat. We evaluated pre-selective enrichment and direct plating protocols using two agar plate media; modified charcoal cefoperazone deoxycholate agar (mCCDA) and blood agar plate through filter membrane (BAF). In the isolation step, two incubation temperatures (37oC, 42oC) in microaerophilic conditions were assessed. The results revealed that pre-selective enrichment protocol had higher sensitivity than direct plating protocol and the optimum incubation was 42oC. Detection limit of artificially inoculated Campylobacter jejuni reference strain in chicken meat isolated on mCCDA and BFA were 10 and 104 CFU/ml respectively. A total of 115 chicken meat samples collected from fresh markets were investigated for Campylobacter spp. contamination. The overall prevalence of C. jejuni that positive by mCCDA or BAF protocol was 12.17% (14/115). In conclusion, pre-selective enrichment step followed by culturing on mCCDA found to be a good protocol for Campylobacter spp. isolation but high flora bacterial contamination was found. The BAF demonstrated an interesting protocol as it is simple, cost-effective and no flora bacterial contamination. Further improvement to get better sensitivity of BAF will be useful for Campylobacter spp. isolation from fresh chicken meat.